LITERATURE REVIEW IN IMPLEMENTATION OF INDUSTRY 4.0 FOR FOOTWEAR INDUSTRY - Eka Legya Frannita; Mochammad Charis Hidayahtullah (Politek ATK Yogyakarta Press, 2023)
Industry 4.0 is an era of digitalization that offers convenience, efficiency and productivity in every field, including of footwear industry. This study aims to investigate the application of technology 4.0 in the footwear industry. This study is mainly discussing about the product cycle of the footwear industry, the distribution map of the application of technology 4.0 in the product cycle of footwear industry, a review of each technology related to footwear industry, as well as the challenges of implementing technology 4.0 in the footwear industry in the future. To reach the significant data, we collect some relevant publications from some reputable publishers in term of the employment of technology for footwear industry. According to the literature results, some technologies such as 3D printing, adaptive manufacturing, automation systems, IoT, augmented reality and artificial intelligence have been employed in the footwear industry. These technologies have been proven to provide benefits such as efficiency and effectiveness of the production process. However, despite technology 4.0 has been proven to provide significant benefits, implementing technology 4.0 still has challenges. The main challenges faced in implementing technology 4.0 are digital data problems, cost issues, connectivity issues and technology literacy issues for the community. Thus, a reasonably in-depth analysis is needed regarding these issues to support the implementation of technology 4.0.